THE CONCEPT OF AL-MAU'IẒAT AND ITS RELEVANCE IN ISLAMIC EDUCATION - Achyar Zein; Syamsu Nahar; Muhammad Fajri Syahroni Siregar; Rahmadi Ali (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
Al-Mau'iẓat is one of the methods used in learning Islamic education. The purpose of this research is to know the concept of al-Mau'iẓat in the Koran and explain how the relevance of the concept of al-Mau'iẓat in Islamic education is expected to add insight into Islamic education. Research by the author is including qualitative research and when collecting data using descriptive and Mawdhu'i methods. The results of this study will be collected and analyzed data and look for relevance in Islamic education. This data will be presented in the descriptive form in the form of sentences. The conclusion is that al-Mau'iẓat is a method that is interpreted as advice used in Islamic Education, and al-mau'iẓat should be done in a kind and gentle manner.